2015
DOI: 10.9781/ijimai.2015.3510
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Applied to Project Success: A Literature Review

Abstract: -Project control and monitoring tools are based on expert judgement and parametric tools. Projects are the means by which companies implement their strategies. However project success rates are still very low. This is a worrying situation that has a great economic impact so alternative tools for project success prediction must be proposed in order to estimate project success or identify critical factors of success. Some of these tools are based on Artificial Intelligence. In this paper we will carry out a lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 44 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…These models, owing to their robust nature, are more accurate than linear models are (e.g. [61], [65]). Furthermore, where there are nonlinear relationships between input and output variables, as well as where there is less information available on the relationships between variables, parametric methods fail to provide an accurate prediction.…”
Section: B Comparison With Previous Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These models, owing to their robust nature, are more accurate than linear models are (e.g. [61], [65]). Furthermore, where there are nonlinear relationships between input and output variables, as well as where there is less information available on the relationships between variables, parametric methods fail to provide an accurate prediction.…”
Section: B Comparison With Previous Methodsmentioning
confidence: 99%
“…In this paper it is found that expert judgment could be used for variable evaluation, adding value to the quality of data collected in key project management areas. Although the complexity of software projects makes using expert judgment difficult to accurately predict the future, the expert judgment itself may be used in conjunction with other methods, such as has been used as an adjustment factor in parametric models [65] or to create Bayesian models [92]. Further, metrics selection based on the expert judgment was a method used in one of the first applications of artificial intelligence to project success, the model of which was created by applying a Bayesian classifier to estimate the project outcome (e.g.…”
Section: B Comparison With Previous Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Algorithms such as naïve Bayes, rule induction, decision tree, boosted decision tree, random forest and stochastic gradient tree boosting have all been used to generate predictions (Mahfouz and Kandil, 2012). Artificial-intelligence algorithms, such as the CI 23,1 Bayesian model, evolutionary fuzzy neural inference model, neural networks, fast messy genetic algorithm, k-means clustering, bootstrap aggregating neural networks and adaptive boosting neural networks, have all been applied to predict project success and to find the critical success factors (Magaña Martínez and Fernandez-Rodriguez, 2015). A model to predict delays in construction logistics was developed using J48 decision tree and naïve Bayes, and the accuracy obtained by both classifiers was compared (Asadi et al, 2015).…”
Section: Machine Learning In Classificationmentioning
confidence: 99%
“…Artificial intelligence (AI) can improve decision-making in complex environments with clear objectives. A study concluded that, in terms of accuracy, artificial intelligence tools outperform traditional tools [5]. The value of AI can only be activated as humans and machines function complementarily integrated.…”
Section: Introductionmentioning
confidence: 99%